The Effect of Pilates Exercises on BDNF Serum Level, Balance and Quality of Life of Menopausal and Non-Menopausal Women - sepide jalali; Hassan Mohammadzade; jalal Dehghanizade (رشد و یادگیری حرکتی ورزشی, 2024)
Introduction: Menopause is the beginning of a new era in a woman's life. This period, like all other stages of life, has positive and negative aspects. The present study aimed to investigate the effectiveness of Pilates exercises on serum BDNF level, balance, and quality of life in menopausal and non-menopausal women.Methods: The current study was a quasi-experimental research with a pre-test and post-test design that included two experimental and two control groups. The sample consisted of 60 menopausal and non-menopausal women (age 45.77±1.77 years) who were voluntarily selected and randomly assigned into four groups of 15 people. Fasting blood was drawn from all the participants 48 hours before the start of training and after the end of the training period. Then both experimental groups performed Pilates exercises for 12 weeks, three sessions per week and each session lasted 60 minutes. Also, the participants similarly performed the Y dynamic balance test and completed the World Health Organization Quality of Life (WHOQOL) questionnaire in pre-test and post-test.Results: The results of Mixed ANOVA showed a significant difference between the pre-test and the post-test of menopausal and non-menopausal women in relevant variables, so it can be said that probably 91%, 76%, and 94% of the changes in serum BDNF levels, balance and quality of life of menopausal and non-menopausal women are influenced by Pilates exercises. However, no significant effect was observed in the relevant variables of control groups (P≤0.05).Conclusion: Pilates exercises can be an effective strategy to improve serum BDNF levels, balance, and quality of life in menopausal and non-menopausal women.